Desain Fasilitas Kerja dan Analisa Kondisi Mikroklimat Berdasarkan Prinsip Ergonomi Guna Meningkatkan Produktivitas Pekerja - Badawi, Ahmad; Sajiyo, Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The research of ergonomic work facility design on the sandal assembly process aims to determine the differences experienced by workers in standard time, workload, musculoskeletal complaints, work fatigue, productivity before and after the design. In addition, an analysis of the microclimate conditions was carried out to determine whether the work space in the sandal assembly process met the standards. The research method used a quantitative method, which is an analysis method in the form of numbers. Data were obtained objectively and subjectively and then analyzed using MS.Excel. and a Paired Sample T test was performed to determine whether the difference results had a significant change. The results showed that there was a difference when using old and new work facilities. It is known that the new design has a positive impact on workers both in standard time, workload, musculoskeletal complaints, work fatigue, and productivity. As well as the microclimate conditions, it is known that temperature, wind speed, and light intensity in the work space do not meet the standards, and only room humidity meets the standards